Characteristics and decision making of hospital report card consumers: lessons from an onsite-based cross-sectional study - Emmert, Martin; Kast, Kristina; Sander, Uwe (Health Policy, 2019)
Background Hospitals report cards (HRCs) have had little impact on the hospital choice of patients. Thus, health policy makers should learn more about HRC consumers to better understand how to present and target hospital-related quality information. Objective We sought to learn more about consumers of HRCs and determine the impact of the complexity and tailoring of HRCs on the hospital choice. Methods We used primary data drawn from an onsite-based survey, conducted in 2017 at Germany’s premier portal, Weisse Liste (N = 635). We performed hierarchical multivariate logistic regression models to identify main predictors associated with hospital choices. Results HRC consumers differ from the national online population and the national population in general. Eighty percent of those patients or family members, who have used a HRC before, confirmed an impact on the hospital choice. The quality of hospital choices decreased with an increasing level of complexity (p < .001); the latter was identified as a significant predictor for making good choices. However, tailoring HRCs did not have an impact on the quality of the hospital choice (p > .05). Conclusions HRCs have a significant impact on the hospital choice among report card consumers. Health policy makers might focus on decreasing the level of complexity; this, more than tailoring report cards, may help consumers make good hospital choices.
Keywords: Public reportingHospital report cardsTailoringSurvey analysis